1974
DOI: 10.1111/j.1440-1827.1974.tb00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycogenosis Type Ii (Pompe)*– The Fourth Autopsy Case in Japan –

Abstract: An autopsy case of glycogenosis type II (Pompe's disease) was reported. The case is that of the fourth autopsy of this type of glycogen storage disease, caused by acid maltase (α‐1, 4‐glucosidase) deficiency, in Japan. In addition to routine histopathological studies on skeletal muscle biopsy and autopsy, also were employed biochemical analyses of the enzyme activities in peripheral white blood cells and skeletal muscle, scoring method of a PAS‐positlve granule In circulating lymphocytes, and electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The pattern of accumulation included neurons and glial cells of the white matter, brainstem, and cerebellum, with relative sparing of cerebellar Purkinje cells. Glycogen accumulation has previously been reported throughout the central nervous system (Araoz et al 1974;Sakurai et al 1974;Asukata et al 1976;Nakamura et al 1979;Teng et al 2004;Thurberg et al 2006). The decedents also had extensive accumulation in anterior horn cells of the spinal cord and in intestinal ganglion cells, as described previously (Thurberg et al 2006;Martini et al 2001;Teng et al 2004).…”
Section: Discussionmentioning
confidence: 86%
“…The pattern of accumulation included neurons and glial cells of the white matter, brainstem, and cerebellum, with relative sparing of cerebellar Purkinje cells. Glycogen accumulation has previously been reported throughout the central nervous system (Araoz et al 1974;Sakurai et al 1974;Asukata et al 1976;Nakamura et al 1979;Teng et al 2004;Thurberg et al 2006). The decedents also had extensive accumulation in anterior horn cells of the spinal cord and in intestinal ganglion cells, as described previously (Thurberg et al 2006;Martini et al 2001;Teng et al 2004).…”
Section: Discussionmentioning
confidence: 86%
“…In infants with Pompe disease, it has been shown that glycogen accumulates in the tongue of an untreated infant (Sakurai et al 1974), but the effect of ERT on bulbar muscle pathology in these infants has not been studied. Only one case report addresses the effect of ERT on bulbar muscle pathology in an adult patient with Pompe disease and showed that, 21 months after treatment with ERT, residual storage of glycogen remained in the oesophagus (Kobayashi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of Pompe disease is heterogeneous and primarily characterized by accumulation of glycogen in skeletal and cardiac muscle associated with progressive skeletal muscle weakness in all variants of the disease and by rapidly progressive hypertrophic cardiomyopathy and early death at about the age of 1 year in patients with the severe infantile variant (Hirschhorn and Reuser 2001;Kishnani and Howell 2004;Kishnani et al 2006a). Glycogen accumulation, however, has also been well documented in central (CNS) and peripheral (PNS) nervous systems (Gambetti et al 1971;Mancall et al 1965;Martin et al 1973;Sakurai et al 1974), also leading to cochlear dysfunction with subsequent hearing loss . In patients with clinical symptoms suggestive for Pompe disease, diagnosis is based on marked reduction of GAA activity in purified peripheral blood lymphocytes (Winchester et al 2008).…”
Section: Introductionmentioning
confidence: 99%